Perubahan Kondisi Sosial Ekonomi Kecamatan Duren Sawit Pasca Pembangunan Banjir Kanal Timur (BKT) - Wafdannida, -; Adriani, Deniza; Rizqy, Natasha Nathaniela (Saskara : Indonesian Journal of Society Studies, 2023)
The flooding that continues to inundate the Duren Sawit District is a long-standing issue. This flood inundates residential areas at a considerable height, making it a flood-prone area. Consequently, the construction of the East Flood Canal (BKT) was undertaken to mitigate the existing floods. The development of BKT resulted in a change in land use from previously established residential, agricultural, and paddy fields. This, in turn, gave rise to social changes in the social and economic sectors, both before and after the implementation of BKT, making it an interesting subject for research. The research method employed in this study is qualitative research, complemented by data collection techniques such as interviews and literature reviews. The findings of this study indicate that BKT functions well in reducing floods as intended during its construction, although some areas still experience flooding. Moreover, BKT has also brought about social and economic changes within the community.